2016
DOI: 10.1177/1071100716681140
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Measurement Error of the Medial Clear Space of the Ankle

Abstract: This high degree of measurement error and lack of precision should be considered when deciding treatment options based on MCS measurements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
0
22
0
1
Order By: Relevance
“…Gougoulias and Sakellariou 8 proposed a theory, based on the anatomy and biomechanical properties of the deltoid ligament, that the deep layer plays a crucial role in fracture stability. Nonetheless, treatment decisions are determined by differences of as little as 1 to 2 mm, and Metitiri et al 17 highlighted the high degree of error and poor accuracy of MCS measurements and suggested that measuring the MCS can be difficult because it relies on the quality of the radiograph and ankle position.…”
Section: Discussionmentioning
confidence: 99%
“…Gougoulias and Sakellariou 8 proposed a theory, based on the anatomy and biomechanical properties of the deltoid ligament, that the deep layer plays a crucial role in fracture stability. Nonetheless, treatment decisions are determined by differences of as little as 1 to 2 mm, and Metitiri et al 17 highlighted the high degree of error and poor accuracy of MCS measurements and suggested that measuring the MCS can be difficult because it relies on the quality of the radiograph and ankle position.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed a mean difference in MCS between paired ankles of 0.6 ± 0.6 mm and thereby recommended routine contralateral radiographic comparison of MCS to assess for pathologic widening in the setting of known anatomic variation and to avoid the potential for false-positives. 45 Further support for the cautious use of an absolute measurement was provided by Metitiri et al 38 Using 3 normal ankle cadaver specimens, the authors transected the deltoid/syndesmotic ligaments and artificially widened the mortise using resin blocks to a defined distance of 4 and 6 mm (the third specimen was left intact). Radiographs were obtained of each cadaver at varying degrees of rotation, and orthopedic providers were asked to measure the MCS using a standardized technique.…”
Section: What Defines An Anatomic Mortise?mentioning
confidence: 99%
“…While previous works have demonstrated near perfect intra-/interobserver agreement when measuring MCS, others have demonstrated poor interobserver agreement. 7,15,17 Furthermore, many previously published studies did not analyze the reliability of measurement or perform any blinding, with the resultant conclusions deemed valid and appropriately clinically relevant. Taking this into consideration, using a single experienced reviewer eliminated potential interobserver discrepancies while relying on previous investigations that appear to obviate the need for intraobserver analysis.…”
Section: Discussionmentioning
confidence: 99%